Volatile Components of Some Selected Turkish Liverworts - Asakawa, Yoshinori; Baser, K. Husnu Can; Erol, Bercu; Von Reuss, Stephan; Konig, Wilfried A.; Ozenoglu, Hatice; Gokler, Isa (SAGE Publications, 2018)
The distribution of liverworts and hornworts in Turkey has been described. The volatile components of the ether extracts of some selected Turkish, Spanish and French liverwort species, Corsinia coriandrina, Lejeunea lamacerina, Lunularia cruciata, Marchantia polymorpha, Metzgeria furcata, Pellia neesiana, Porella cordaeana, Porella platyphylla and Scapania undulata were analysed by GC-MS. C. coriandrina produces isothiocyanates and S, Sdimethyliminodithiocarbonates similar to those isolated from the marine hydroid, Tridentata marginata. The species also produces the characteristic 2- arylbenzofurans. L. lamacerina is closely related chemically to the Japanese Lejeunea aquatica, L. flava and L. japonica since it elaborates the same cuparene sesquiterpenoids as those found in the latter three species.
Keywords: Turkish liverworts; Volatile components; Corsinia coriandrina; Isothiocyanates; Iminodithiocarbonates; Stilbenes; Bibenzyls.